Analysis Knowledge of PJKR Student Scientific Journal Articles - Novita Novita; Nurkadri Nurkadri; Harly Nugraha; Bernad simanjuntak (Universitas Suryakancana, 2022)
In this era of globalization, the education system is an important matter that needs special attention, one of which is in Indonesia. This era of globalization also requires the ability that students need to have to develop their academic activities, namely learning and writing a work, whether in the form of poetry, rhymes, books, or scientific papers. That way, the ability to write must be possessed by everyone who is engaged in education, one of which is students. Research can be interpreted as a way to answer problems or questions by collecting data and formulating generalizations based on this data, especially regarding physical education. The purpose of this study was to determine the knowledge of PJKR FIK Unimed students in writing scientific articles. This research method uses descriptive quantitative. The population in this study were PJKR FIK UNIMED students. The sample in this study were 2016-2022 PJKR FIK UNIMED students, namely 1,002 students who were still actively studying. The sampling technique used is purposive sampling. The data collection method uses a survey method in the form of a questionnaire. Data from the results of the test instrument were processed using descriptive analysis methods. The results of the analysis show that 50% of PJKR FIK UNIMED students know about scientific journal articles and get materials related to scientific journal articles in lectures, but more than 50% do not know the steps for writing scientific journals until the publish stage.Key words: Analysis, Knowledge, Health Physical Education and Recreation, ScientificJournals.